The value of low- and negative-carbon fuels in the transition to net-zero emission economies: Lifecycle greenhouse gas emissions and cost assessments across multiple fuel types. (1st February 2023) - Cheng, Fangwei; Luo, Hongxi; Jenkins, Jesse D.; Larson, Eric D.
Highlights: 16 lifecycle pathways for low- or negative-carbon H2, liquid fuel, and synthetic natural gas production from biomass, electricity, and natural gas feedstocks are analyzed. Hydrogen pathways are less costly to decarbonize than liquid fuel and synthetic gas pathways for the same input feedstock. Gasification-based production from biomass coupled with carbon capture and storage is particularly attractive in the presence of carbon emission prices. Abstract: In recent macro-energy systems modeling studies of net-zero emissions pathways for the United States and elsewhere, fuels made via gasification of sustainably produced biomass coupled with carbon capture and storage (CCS) play critical roles in achieving economy-wide net-zero greenhouse gas emissions because they provide carbon-negative energy carriers. In this study, we develop lifecycle greenhouse gas (GHG) emissions and cost assessments to provide insights into the environmental and economic cost and value of hydrogen (H2 ), synthetic natural gas (SNG), and Fischer-Tropsch liquid (FTL) fuels made from 1) biomass, coupled with CCS, 2) natural gas, with CCS, and 3) renewably-generated electricity. We find that H2 production pathways are less costly to decarbonize than FTL and SNG pathways that use the same input feedstock and also provide the largest reductions in lifecycle GHG emissions per unit of delivered fuel. Sensitivity analyses on the levelized costs of carbon mitigation (LCCM) indicate that capital costs and capacity factors are influential for most of the pathways. Costs for processes that use natural gas as feedstock are more sensitive to changes in input feedstock intensity than other processes. Finally, we find that fuel production pathways starting from biomass and including CCS have the highest carbon mitigation potentials among all feedstock pathways. They also have the lowest production costs beyond certain threshold carbon emission price levels. Our findings help explain the critical role that biomass-based hydrogen production with CCS plays in macro-energy system models of the U.S. transition to net-zero emissions.